Factors that influence employee motivation at Majlis Daerah Kuala Karai (MDKK) / Mohd Lukman Muhamad - Muhamad, Mohd Lukman (2019)
The main objective of this study is to investigate factors influencing employees’ motivation at Majlis Daerah Kuala Krai (MDKK). Three independent variables; communication, work environment and performance appraisal has been chosen by the researcher as predictors to employee motivation in this study. This research is conducted at MDKK and 108 employees were chosen as the respondents for this study. The questionnaires were used to collect the data and the data obtained from the respondents are analyzed using Statistical Package for Social Science (SPSS) software. The result from the analysis revealed that there is a significant relationship between independent variables which are communication, work environment, performance appraisal and employee motivation. Other than that, this study also provides recommendations for the organization, employees and also for future researchers to help them improve and solve the problem regarding employee motivation.